Animation and graphical model for crowd simulation - Khadafi, Muhammad. (2010)
Video game industry is an actively advancing industry in terms of advancement in hardware and graphical software. One of the most important feature in modern videogame is the graphical interface, whether it is the commands or the game word, is it the things that the player see with their own eyes. A computer game that requires a persistent game world with a lot of players (active / non-active) such as the Massively Multiplayer Online, or an adventure game consists of crowds of multiple objects and characters or avatars, therefore requires an effective way to create and manage the crowds’ diversity while keeping the game load at a minimum and for the best overall performance.